2019
DOI: 10.1177/2325967119827237
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Progen, a Nutritional Supplement Based on Innovative Plasma Proteins, in ACL Reconstruction: A Multicenter Randomized Controlled Trial

Abstract: Background: New biologic strategies are arising to enhance healing and improve the clinical outcome of anterior cruciate ligament (ACL) reconstruction. Purpose: To evaluate the efficacy of a new oral nutritional supplement (Progen) that contains hydrolyzed collagen peptides and plasma proteins, a hyaluronic acid–chondroitin sulfate complex, and vitamin C. Study Design: Randomized controlled trial; Level of evidence, 2. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Whilst the results of Lopez-Vidriero et al [12] and Seijas et al [28] are in agreement, it should be highlighted that the comparison of these results proves difficult due to different forms of PRP being used; Lopez-Vidriero et al [12] provided oral supplementation of PRP, Seijas et al [28] using simple injectable PRP and Valenti Nin et al [22] using PDGF gel. On the other hand, the use of different preparations of PRP may help in determining which form is most suited in improving ligamentization rates.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Whilst the results of Lopez-Vidriero et al [12] and Seijas et al [28] are in agreement, it should be highlighted that the comparison of these results proves difficult due to different forms of PRP being used; Lopez-Vidriero et al [12] provided oral supplementation of PRP, Seijas et al [28] using simple injectable PRP and Valenti Nin et al [22] using PDGF gel. On the other hand, the use of different preparations of PRP may help in determining which form is most suited in improving ligamentization rates.…”
Section: Discussionmentioning
confidence: 73%
“…No significant difference was found beyond 6 months. Seven studies [11,12,[15][16][17][18]22] evaluated knee function, two of which found PRP to improve overall knee function [11,12]. No significant difference was found beyond 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations